2006
DOI: 10.1074/jbc.m509134200
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin S Controls Angiogenesis and Tumor Growth via Matrix-derived Angiogenic Factors

Abstract: The cysteine protease cathepsin S is highly expressed in malignant tissues. By using a mouse model of multistage murine pancreatic islet cell carcinogenesis in which cysteine cathepsin activity has been functionally implicated, we demonstrated that selective cathepsin S deficiency impaired angiogenesis and tumor cell proliferation, thereby impairing angiogenic islet formation and the growth of solid tumors, whereas the absence of its endogenous inhibitor cystatin C resulted in opposite phenotypes. Although mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
204
2
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 251 publications
(218 citation statements)
references
References 50 publications
7
204
2
5
Order By: Relevance
“…Cysteine cathepsins are commonly reported to participate to and enhance cell growth, migration, invasion, angiogenesis, and metastasis, and comprehensible relationships have been established between their deregulation and cancer progression (25,26,38). For instance, cathepsin S, which can degrade anti-angiogenic collagen IV-derived peptides and release proangiogenic fragments from laminin, has been described to favor angiogenesis and microvessel formation in physiological neovascularization (39). Nevertheless, our current perception of the role of cathepsins is evolving.…”
Section: Discussionmentioning
confidence: 99%
“…Cysteine cathepsins are commonly reported to participate to and enhance cell growth, migration, invasion, angiogenesis, and metastasis, and comprehensible relationships have been established between their deregulation and cancer progression (25,26,38). For instance, cathepsin S, which can degrade anti-angiogenic collagen IV-derived peptides and release proangiogenic fragments from laminin, has been described to favor angiogenesis and microvessel formation in physiological neovascularization (39). Nevertheless, our current perception of the role of cathepsins is evolving.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it is well known that, among three glycoprotein subunits of laminin-5 (a3, b3 and g2), g2 chain-derived fragments promote cancer cell migration, invasion and associated vasculogenesis 28,29 . CatS deficiency has been shown to reduce processing of laminin-5 g2-derived fragments in a mouse tumour model 11 . In contrast, a deficiency of its endogenous inhibitor, cystatin C, promotes tumour growth by enhancing g2-derived fragment production 26 .…”
Section: Expression Of Catk In Ecsmentioning
confidence: 99%
“…In addition, except for Jagged-1, ischaemic injury increased all targeted molecules in CatK þ / þ and CatK À / À mice. Multiple studies have demonstrated that Cats (CatS and CatL) participate in the release of the extracellular matrix and basement membrane-derived growth factors, either by converting them from their latent forms or degrading their associated inhibitors 11,27 . Endostatin is a proteolytic fragment of type XVIII collagen generated by several proteases in vivo, including Cats and MMPs.…”
Section: Expression Of Catk In Ecsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, cathepsin S-deficient mice showed decreased susceptibility to collagen-induced arthritis (14), and rats with adjuvant-induced arthritis displayed significant decreases in inflammation after oral administration of the cathepsin S inhibitor LHVS (16), not only supporting a specific role for CatS in rheumatoid arthritis but also validating CatS as an appropriate drug target in other autoimmune disorders. CatS has recently emerged as an important proteolytic enzyme in cancer development, and CatS inhibitors have been proposed as anticancer agents (17,18). Compounds targeting CatS in rheumatoid arthritis, bronchial asthma, and psoriasis are already undergoing clinical evaluation, and the development of new CatS inhibitors is still a growing field (19).…”
mentioning
confidence: 99%